The endogenous cannabinoid system modulates male sexual behavior expression - Rodríguez-Manzo, Gabriela; Canseco-Alba, Ana (Frontiers in Behavioral Neuroscience, 2023)
The endocannabinoid system (ECS) plays a key neuromodulatory role in the brain. Main features of endocannabinoids (eCBs) are that they are produced on demand, in response to enhanced neuronal activity, act as retrograde messengers, and participate in the induction of brain plasticity processes. Sexual activity is a motivated behavior and therefore, the mesolimbic dopaminergic system (MSL) plays a central role in the control of its appetitive component (drive to engage in copulation). In turn, copulation activates mesolimbic dopamine neurons and repeated copulation produces the continuous activation of the MSL system. Sustained sexual activity leads to the achievement of sexual satiety, which main outcome is the transient transformation of sexually active male rats into sexually inhibited animals. Thus, 24 h after copulation to satiety, the sexually satiated males exhibit a decreased sexual motivation and do not respond to the presence of a sexually receptive female with sexual activity. Interestingly, blockade of cannabinoid receptor 1 (CB1R) during the copulation to satiety process, interferes with both the appearance of the long-lasting sexual inhibition and the decrease in sexual motivation in the sexually satiated males. This effect is reproduced when blocking CB1R at the ventral tegmental area evidencing the involvement of MSL eCBs in the induction of this sexual inhibitory state. Here we review the available evidence regarding the effects of cannabinoids, including exogenously administered eCBs, on male rodent sexual behavior of both sexually competent animals and rat sub populations spontaneously showing copulatory deficits, considered useful to model some human male sexual dysfunctions. We also include the effects of cannabis preparations on human male sexual activity. Finally, we review the role played by the ECS in the control of male sexual behavior expression with the aid of the sexual satiety phenomenon. Sexual satiety appears as a suitable model for the study of the relationship between eCB signaling, MSL synaptic plasticity and the modulation of male sexual motivation under physiological conditions that might be useful for the understanding of MSL functioning, eCB-mediated plasticity and their relationship with motivational processes.